2020
DOI: 10.1155/2020/2681791
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Microbiota and Inorganic Anion Content in the Saliva of Patients with Gastroesophageal Reflux Disease and Gastroesophageal Reflux Disease-Free Individuals

Abstract: The oral cavity is one of the most complex microbial environments; however, the complex nature of the salivary microbiota and the level of inorganic anions in the saliva of subjects with and without gastroesophageal reflux disease (GERD) are poorly understood. The primary goals of this pilot research were to assess differences in salivary bacterial community composition and inorganic anion concentrations between patients with GERD and GERD-free people. Thus, the salivary microbiota within both groups was domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…Bicarbonate level influences salivary pH and pH increase as bicarbonate concentration increase, but non-stimulated saliva insufficiently buffered because bicarbonate level is too low to be effective [32]. Based on the present results, no significant difference was found in salivary phosphate between established groups and this result was agreed with other studies [33].…”
Section: Laboratory Findingssupporting
confidence: 91%
“…Bicarbonate level influences salivary pH and pH increase as bicarbonate concentration increase, but non-stimulated saliva insufficiently buffered because bicarbonate level is too low to be effective [32]. Based on the present results, no significant difference was found in salivary phosphate between established groups and this result was agreed with other studies [33].…”
Section: Laboratory Findingssupporting
confidence: 91%
“…Several studies have identified increased abundances of the oral microbe Fusobacterium in setting of colorectal cancer ( 29 , 33 35 ), liver cirrhosis ( 36 38 ), primary sclerosing cholangitis ( 39 41 ), gastroesophageal reflux disease ( 42 46 ), HIV infection ( 47 49 ), alcoholism ( 50 ), and IBD ( 6 , 10 19 ). Given the prevalence of F. nucleatum in mucosal specimens, we tested the hypothesis that this pathobiont could promote an epithelial proinflammatory response and potentially contribute to intestinal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Amplicon sequencing was conducted using an Illumina MiSeq system with 2 × 300 bp reads. The sequence data were then analyzed as detailed previously [ 15 , 20 , 21 , 22 ] and available on request.…”
Section: Methodsmentioning
confidence: 99%